Flexor reflex decreases during sympathetic stimulation in chronic human spinal cord injury - Garrison, M. Kevin (2009)
A better understanding of autonomic influence on motor reflex pathways in spinal cord injury is important to the clinical management of autonomic dysreflexia and spasticity in spinal cord injured patients. The purpose of this study was to examine the modulation of flexor reflex windup during episodes of induced sympathetic activity in chronic human spinal cord injury (SCI). We simultaneously measured peripheral vascular conductance and the windup of the flexor reflex in response to conditioning stimuli of electrocutaneous stimulation to the opposite leg and bladder percussion. Flexor reflexes were quantified using torque measurements of the response to a noxious electrical stimulus applied to the skin of the medial arch of the foot. Both bladder percussion and skin conditioning stimuli produced a reduction (43-67%) in the ankle and hip flexor torques (p<0.05) of the flexor reflex. This reduction was accompanied by a simultaneous reduction in vascular conductance, measured using venous plethysmography, with a time course that matched the flexor reflex depression. While there was an overall attenuation of the flexor reflex, windup of the flexor reflex to repeated stimuli was maintained during periods of increased sympathetic activity. This paradoxical depression of flexor reflexes and minimal effect on windup is consistent with inhibition of afferent feedback within the superficial dorsal horn. The results of this study bring attention to the possible interaction of motor and sympathetic reflexes in SCI above and below the T5 spinal level, and have implications for clinicians in spasticity management and for researchers investigating motor reflexes post SCI.